Appraisal of residential satisfaction in double-storey terrace housing in Kuala Lumpur, Malaysia - Mohit, Mohammad Abdul; Adel Mahfoud, Al-Kahnbashi (Elsevier Ltd., 2015)
Double-storey terrace housing is considered as a popular housing type in Malaysia. However, empirical studies identified that, an increase in crime rate in urban areas has affected on residents' satisfaction of landed housing such as double-storey terrace house. In addition, design of double-storey terrace house lacks ventilation and natural lighting which have also affected on residents' satisfaction. As a result of residents' dissatisfaction, double-storey terrace house is found as the most modified housing types in Malaysia. Thus, this paper aims to appraise residential satisfaction in two double-storey terrace neighbourhoods - Taman Sri Rampai and Taman Keramat Permai in Greater Kuala Lumpur. The research objectives were formulated based on a dynamic interaction approach which includes three main processes - cognitive, affective and behavioural. In order to examine and compare the residential satisfaction in two neighbourhoods, five components of double-storey terrace housing were analyzed through residents’ perception on the level of satisfaction. The recommendations of the study suggests that two housing design and five neighbourhood elements can enhance residents' satisfaction with double-storey terrace housing.